1980
DOI: 10.1037/0033-2909.87.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Tests for comparing elements of a correlation matrix.

Abstract: small-sample performance and computational efficiency. Several techniques are illustrated with numerical examples.-Pjl? -Pjft 2 -Pkl?)-(3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
2,961
8
25

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,026 publications
(3,037 citation statements)
references
References 14 publications
43
2,961
8
25
Order By: Relevance
“…The standard deviation of the true score correlations was smaller for organizational-targeted behaviors, but it was not much different for individual-targeted behaviors, (SD ϭ .07 and SD ϭ .12, respectively) compared with the overall analysis (SD ϭ .11). A Hotelling-Williams test, recommended when comparing nonindependent correlations that share a variable (see Steiger, 1980), showed that the two correlations were significantly different from each other. Whether LMX and citizenship behavior ratings were provided by the same source substantially influenced the meta-analytic correlation between the two constructs: The estimate for samesource ratings was ϭ .54, whereas the meta-analytic correlation between these constructs was ϭ .32 when different raters provided the two construct scores.…”
Section: Resultsmentioning
confidence: 99%
“…The standard deviation of the true score correlations was smaller for organizational-targeted behaviors, but it was not much different for individual-targeted behaviors, (SD ϭ .07 and SD ϭ .12, respectively) compared with the overall analysis (SD ϭ .11). A Hotelling-Williams test, recommended when comparing nonindependent correlations that share a variable (see Steiger, 1980), showed that the two correlations were significantly different from each other. Whether LMX and citizenship behavior ratings were provided by the same source substantially influenced the meta-analytic correlation between the two constructs: The estimate for samesource ratings was ϭ .54, whereas the meta-analytic correlation between these constructs was ϭ .32 when different raters provided the two construct scores.…”
Section: Resultsmentioning
confidence: 99%
“…6). Steiger’s Z-Test 39 shows that activity inequality is more strongly correlated with obesity than the average volume of steps recorded in a country (r = 0.79 vs. −0.62; N = 46; t = 2.86; p < 0.01). For example, even though the United Kingdom has higher average daily steps than Germany and France (5444 vs. 5205 and 5141), it exhibits higher obesity prevalence (19.5% vs. 14.3% and 8.9%).…”
Section: Methodsmentioning
confidence: 99%
“…The correlations were calculated separately from planar dGEMRIC map-dependent data and planar map-independent data, and 95% confidence intervals and p values were presented for each using the Fisher Z-transformation approach. We tested whether the correlations with versus without the use of the planar maps differed from each other using methods in either Meng et al [16] or Steiger [20] depending on whether the pairs of correlated measures being compared had one measure in common. When comparing the planar map-dependent and map-independent Beck-Outerbridge correlations as well as map-dependent and map-independent Beck-dGEMRIC correlations, the same Beck's grades are used in every correlation and so the methods of Meng et al were used.…”
Section: Methodsmentioning
confidence: 99%